Silage additives improve fermentation quality, aerobic stability and rumen degradation in mixed silage composed of amaranth and corn straw - Ma, Jian; Fan, Xue; Ma, Zhuang; Huang, Xiuwen; Tang, Minghuan; Yin, Fuquan; Zhao, Zhihui; Gan, Shangquan (Frontiers in Plant Science, 2023)
The objective of this research was to investigate effects of different additives on the fermentation quality, aerobic stability and rumen degradation of mixed silage composed of amaranth and corn straw. The mixture ratio of amaranth to corn straw was 78% : 22%. Three additives were selected in this study and five groups were as follows: control group (CON, without additive), lactic acid bacteria group (LAB, 5 mg/kg, Lactobacillus plantarum ≥ 1.6×1010 CFU/g and L. buchneri ≥ 4.0×109 CFU/g), glucose group (GLU, 30 g/kg), cellulase group (CEL, 2 mg/kg) and lactic acid bacteria, glucose and cellulase group (LGC, added at the same levels as in individual group). The period of ensiling was 60 days. Fermentation quality, chemical composition and aerobic stability of mixed silage were analyzed. Four cows with permanent ruminal fistula were selected as experimental animals. Nylon bag technique was used to study rumen degradation characteristic of dry matter (DM), crude protein (CP), neutral detergent fiber (NDF) and acid detergent fiber (ADF) of mixed silage. Compared with CON group, the addition of different silage additives could improve mixed silage quality of amaranth and corn straw to some extent. Combining three additives significantly increased (P < 0.05) the DM, CP and lactic acid contents, whereas decreased (P < 0.05) the ADF and NDF contents as well as pH and ammonia nitrogen/total nitrogen. Moreover, the aerobic stability and rumen degradation of DM, CP and NDF were significantly improved (P < 0.05) in LGC group when compared to other groups. In conclusion, the combined addition of lactic acid bacteria, glucose and cellulase increased DM, CP and lactic acid contents as well as lactic acid bacteria count, decreased NDF and ADF contents and aerobic bacteria and mold counts, improved aerobic stability and rumen degradation of amaranth and corn straw mixed silage.